Ramifications of Industrial Pollution: Problems and Ways to Fix Them - Dr. N. Subbu Krishna Sastry; Dr. V. Basil Hans (International Journal of Pollution: Prevention & Control, 2025)
Pollution from industry is still one of the largest environmental challenges of the 21st century. It hurts the air, water, and land all around the world. This page discusses about the primary kinds of pollutants that arise from factories, such as heavy metals, particles, and toxic chemicals. It studies at how industrial emissions affect people and the environment, such as by causing respiratory problems, harming ecosystems, and changing the climate. Some of the difficulties caused by industrial pollution are health problems, damage to the environment from dirty air, water, and soil, loss of biodiversity, and climate change. Implementing stronger environmental rules, using clean technologies and renewable energy sources, improving waste management, encouraging recycling, choosing the right places for industry, planting trees, and raising public awareness are all ways to solve the problem.The article also talks about the current rules and regulations, new technologies, and eco-friendly ways of doing things that are supposed to cut down on pollution. To maintain the environment for the long term, it's vital to make things in a way that is good for the environment, reduce waste, and hold businesses accountable. The essay talks about both the difficulties and the potential ideas that could help industry become cleaner and more sustainable. Green Technology, Industrial Emissions, Environmental Impact, Pollution Control, Sustainable Practices, and Regulatory Frameworks are some of the words that come to mind.
Keywords: Environment; Industrial pollution; cleaner technology; economy; resources